An electrospray ionization study on complexes of amylin with Cu(II) and Cu(I). (13th June 2021) - Moracci, Laura; Crotti, Sara; Traldi, Pietro; Cosma, Chiara; Lapolla, Annunziata; Pucciarelli, Salvatore; Agostini, Marco
Abstract: Human amylin (hIAPP) is one of a number of different peptides known to be responsible for the formation of amyloid fibrils in the pancreas of subjects with Type 2 diabetes mellitus. It was recognized that metal ions such as Cu(II) are implicated in the aggregation process of amyloidogenic peptides. However, the role of Cu(II) ions in the aggregation and dyshomeostasis of amylin has been controversial. Considering that most of the research reported in the literature pertain to the interactions between Cu(II) and amylin, we thought of interest to compare the interactions of Cu(II) and Cu(I) ions with amylin by electrospray ionization (ESI) mass spectrometry and collisional experiments, to elucidate possible differences in structural aspects of the complexes so formed. The ESI mass spectra of solutions containing hIAPP and Cu(I) or Cu(II) ions show the formation of hIAPP–Cu complexes. In both cases, M + Cu ions with three and four positive charges are detected. However, a series of fragment ions, absent in the ESI spectrum of untreated hIAPP, become detectable. Some of them are common for both Cu(I) and Cu(II) complexes, whereas others are specific for the complexes containing Cu in different oxidation states. Some fragments imply the involvement of residues His18, Ser19, Ser20, Asn21, and Asn22 in the complex formation, but the detection of the fragment b22 3+ indicates the presence of copper ions in a different position. This suggests different interaction sites between Cu(II) and Cu(I) and hIAPP. In contrast to Cu(II) complex, in the Cu(I) complex, some peculiar structures are present, corresponding to the cleavage of Asn–Asn peptidic bond and to [b30  + Cu(I)] 4+ and [b28  + Cu(I)] 4+ species. These results are in agreement with the coordination vacancy in [Cu(I)–(peptide)] species, which promotes Cu(I) interaction with additional neighboring donors (mainly N‐histidine, and also S‐methionine or other groups depending on the peptide conformation) through formation of trigonal T‐shaped intermediates.